Overcoming efficiency and cost barriers for large-area quantum dot photovoltaics through stable ink engineering - Shi, Guozheng; Ding, Xiaobo; Liu, Zeke; Liu, Yang; Chen, Yifan; Liu, Cheng; Ni, Zitao; Wang, Haibin; Ito, Katsuji; Igarashi, Keisuke; Feng, Kun; Zhang, Kaicheng; et al. (Nature Energy, 2025)
The bottom-up construction of electronics from colloidal quantum dots (CQDs) could innovate nanotechnology manufacturing through printing. However, the unstable and expensive semiconductive CQD inks make the scaling up of CQD electronics challenging. Here we develop a strategy for engineering the solution chemistry of lead sulfide (PbS) CQD inks prepared from a low-cost direct synthesis method. By creating an iodine-rich environment in weakly coordinating solvents, we convert the iodoplumbates into functional anions, which condense into a robust surface shell. The fully charged electrostatic surface layer prevents aggregation and epitaxial fusion of CQDs, yielding stable inks. By eliminating the fusion-induced inter-band states, we print a compact CQD film with uniformity in three dimensions, flattened energy landscape and improved carrier transport. We achieved a certified efficiency of 13.40% on 0.04 cm2 cells, with a 300-fold increase in active area, scaling up to a 12.60 cm2 module with a certified efficiency of 10%.
CRIS-Team Scopus Importer:2025-04-18